Proximal Parent Vessel Tapering is Associated With Aneurysm at the Middle Cerebral Artery Bifurcation. Issue 5 (26th May 2018) - Lauric, Alexandra; Greim-Kuczewski, Kilian; Antonov, Alexei; Dardik, Gabriel; Magida, Jane K; Hippelheuser, James E; Kono, Kenichi; Malek, Adel M
Abstract: BACKGROUND: Cerebral aneurysm initiation and evolution have been linked to hemodynamic and morphological factors. Stenotic morphology upstream to a bifurcation can alter hemodynamic patterns and lead to destructive vessel wall remodeling and aneurysm initiation. The effect of more subtle proximal variations in vessel diameter on bifurcation aneurysm development has not been evaluated. OBJECTIVE: To investigate whether vessel tapering is associated with aneurysmal presence at the middle cerebral artery (MCA) bifurcation. METHODS: Bilateral catheter three-dimensional rotational angiographic datasets from 33 patients with unilateral unruptured MCA aneurysms and 44 datasets from healthy patients were analyzed. Equidistant cross-sectional cuts were generated along the MCA M1 segment with cross-sectional area measurement using edge-detection filtering. Relative tapering of the M1 segment was evaluated as the TaperingRatio. Computational fluid dynamics (CFD) simulations were performed on bilateral patient models and parametric MCAs of constant and tapered inflow vessel. RESULTS: MCA leading to aneurysms had significantly lower TaperingRatio (0.88 ± 0.15) compared to contralateral (1.00 ± 0.16, P = .002) and healthy MCAs (1.00 ± 0.15, P > .001, area under the curve = 0.73), which showed little to no tapering. CFD simulations showed that vessel tapering leads to flow acceleration with higher wall shear stress (WSS) and WSS gradients at the bifurcation apex. CONCLUSION: Aneurysmal but not contralateral or control MCA M1 segments demonstrate a previously undescribed progressive distal tapering phenomenon. This upstream vessel narrowing leads to flow acceleration that accentuates WSS and spatial gradients at the bifurcation apex, a pattern previously shown to favor aneurysm initiation and progression.